A pedagogical Approach for Integrating Smartphones into Learning Activities: Evidence Based Practice at Secondary School (British Journal of Multidisciplinary and Advanced Studies, 2026)
Research in emerging technologies has argued that the pedagogical integration of smart-phones in learning activities is important to engage students in meaningful learning experiences. Recent studies have shown that SOAR pedagogy is effective when implemented in social science environments.  Some of empirical studies of SOAR based mobile learning have demonstrated examples of different learning scenarios with positive results toward students’ performance. However, there is a little research exploring the augmentation of SOAR based mobile devices in field of science learning environments. This research is based on an experimental study where participants were divided to the experimental group (EG), (n = 33) who employed SOAR with mobile devices and control group (CG), (n =33) who followed mobile without SOAR approach. The purpose was to examine and compare the effectiveness of two mobile learning approaches on improving students’ learning achievement. In particular, EG group engagement and perspectives are investigated as to explore whether the mobile SOAR approach had positive effect on learning activities. The study was carried out in a secondary school located in Khartoum state in Sudan, both quantitative and qualitative techniques were employed to collect and analyze the data in order to understand the variations between two pedagogical approaches. Our results indicated that significant differences existed between students learning achievement, the EG students’ achievement was significantly higher compared to CG students.  Moreover, the EG students reported that the mobile SOAR approach has influenced their engagement and create positive perspectives toward learning activities. We conclude by arguing that, diverse learning technology environments, and large sample size are critical to explore the potential of mobile SOAR approach in improving students learning performance.